Effects of Ripeness and Blending Speed on the Extraction Yield and Physical Chemical Properties of Low Viscosity Banana Juice - Kibazohi, Oscar; Matabura, Victor V (Tanzania Journal of Science, 2021)
Low viscosity banana juice can be extracted from banana by blending and pressing the resulted semi-solid pulp to separate the juice. This juice extraction technology is relatively new and further studies to understand key parameters for juice release is vital for scaling up production and commercialisation. This study, investigated the influence of blending speed and ripeness stage on banana juice yield using two banana cultivars; the East African highland banana (Mbile) and the exotic banana (Pisang awak). Types of sugars and organic acids in the juice were analysed using an HPLC. Changes with ripening of fruit firmness, juice pH and soluble solids were also examined. The juice yield increased significantly (p < 0.05) with increasing blending speed and ripeness stage for all cultivars. The Mbile cultivar from Kagera had the highest juice yield of 82.35%, followed by Mbile cultivar from Kilimanjaro with 75.30% and Pisang awak cultivar with juice yield of 62.50%. The highest juice yield for all cultivars was achieved at 3500 rpm blending speed and ripeness stage 5. Fructose and glucose sugars increased significantly (p < 0.05) with ripeness, while sucrose showed insignificant changes. Malic and citric acids were observed to increase significantly (p < 0.05) during ripening in all banana cultivars. Keywords: East African highland banana, Banana juice extraction, Blending speed, Low viscosity banana juice.